KAJIAN PENDAPATAN USAHATANI DAN KARAKTERISTIK PADI LOKAL (Oriza sativa L) VARIETAS SIAM ARJUNA DI LAHAN PASANG SURUT DI DESA NUSA INDAH KECAMATAN BATI BATI - Zulipah Mahdalena; Zuraida; Fransisko Lae (Chlorophyl, 2026)
This study aims to examine the costs, revenue, and income associated with the cultivation of the local Siam Arjuna rice variety, as well as to study the characteristics of this local rice variety. The research method used was purposive sampling, with 25 farmers selected as the sample. The results of this study showed an average yield of 5,328 kg per farmer, or 4.2 tons per hectare. Average revenue was Rp40,488,000 per farmer, while average income was Rp39,514,877 per farmer.. The characteristics of the local Siam Arjuna rice variety cultivated in Nusa Indah Village are essentially no different from those of the variety in general, with a potential yield of 4.2 tons per hectare. This indicates that the local Siam Arjuna rice variety is highly adaptable and can be successfully cultivated in Nusa Indah Village